Kebutuhan Kalsium Ayam Broiler Fase Starter dengan Penambahan Enzim Fitase - Eny Sholikhatin; Ferry Poernama; Nanung Danar Dono; Zuprizal . (Buletin Peternakan, 2016)
The aim of this study was to determine the calcium requirements of broiler chickens in starter phase with the addition of phytase enzyme. This experiment used 1,200 broiler chickens (mixed sex) for 21 days rearing period in a closed house. The basal diets was corn and soybean meal which contained 0.097% Ca and 0.123% P-av. The treatments consisted of 6 diets treatment: P1 (basal diet with the addition of 0.42% non-phytate phosphorus (NPP), and then P2 to P6 were basal diet with the addition of 0.22% NPP and 1,000 FTU/kg phytase and the addition of calcium (Ca) at different levels: 0.82% (P2); 0.74% (P3); 0.66% (P4); 0.58% (P5) and 0.50% (P6). The growth performance, feed efficiency, and bone mineralization parameters were studied using Oneway ANOVA in a Completely Randomized Design. Duncan's new Multiple Ranges Test was used to separate means with significant differences. Results showed that 0.90% Ca supplementation without phytase and the reduction levels of Ca from 0.82% to 0.50% increased the amount of feed consumed by birds in all growth phases (P<0.05). The addition of phytase had beneficial effects on increasing body weight (P<0.05) and average of body weight gain (P<0.05), and decreased the value of FCR in 11 - 21 days and 1 - 21 days. The addition of phytase increased protein and energy consumption, followed by increased in the value of PER and  EER (P<0.05). When phytase was added in the diets, reduction levels of Ca in the diets up to 0.50% did not give any adverse effect on the tibia bone ash. It can be concluded that feeding with phytase can sustain growth performance, feed efficiency, and bone mineralization.